Public Mosquito Abatement : A Cluster Randomized Experiment - Thuilliez, Josselin; Dumont, Yves (World Bank, Washington, DC, 2017)
Mosquito abatement is a public good. A simultaneous model of mosquito abundance and abatement response is developed. This paper uses data from a cluster randomized controlled experiment conducted over the period 2012-2014 in urban areas of Reunion in France to study the impact of WHO-recommended mechanical elimination techniques, which involve removing sources of stagnant water around the house, on a number of outcomes, including objective entomological indices and self-declared protective behaviors. Empirical results document that households reduce their protective behavior in response to public control. This study holds implications for arboviral disease control, including Zika control.